PERILAKU PETANI DALAM MENGHADAPI FLUKTUASI HARGA USAHATANI DI TENGAH PANDEMI CORONA VIRUS COVID 19 DI KABUPATEN DAIRI - Roida Ervina Sinaga; Sumatera Tarigan (JURNAL REGIONOMIC, 2020)
The aim of this study is to analyze the behavior of farmers in dealing with price fluctuations in situation of covid-19. This method used is qualitative in which this study intends to describe and interpret a condition. This research location was carried out purposively in several village in Sidikalang district of Dairi regency. Data collected through interviews with several questionnaires.The result obtained include among others the area of land worked, age of farmers, number of dependent of farmers per month, level of education, commodity price, fertilizer prices and performance during the pandemic..Based on the research results that have been explained, the researcher concludes that the price of commodities during the pandemic has decreased, although the performance of the farmers remains.